Hypervitaminemia B12 in the elderly: a forgotten marker of serious underlying diseases - Abrar-Ahmad Zulfiqar (European Journal of Case Reports in Internal Medicine)
Hypervitaminemia B12, long neglected in clinical practice, is a biological anomaly whose pathological significance remains largely underestimated, particularly in the elderly. While medical attention has historically focused on vitamin B12 deficiency, several recent studies suggest that elevated levels of this vitamin may reveal serious underlying pathologies, such as solid neoplasia, haematological malignancies, chronic liver disease or renal failure. We report the case of a 91-year-old man hospitalized for asthenia, anorexia and altered general condition, in whom vitamin B12 assay revealed major hypervitaminemia (1318 pg/ml). The work-up revealed hepatic cirrhosis of alcoholic origin, complicated by hepatocellular carcinoma which was metastatic from the outset. This case illustrates the potential prognostic value of vitamin B12 dosage, particularly when coupled with C-reactive protein (BCI index), a high value (> 40,000) of which is associated with short-term mortality in patients with advanced cancer. Beyond hepatopathy, hypervitaminemia B12 is associated in the literature with increased haptocorrin release in myeloproliferative syndromes, excess transcobalamins in renal failure, or paradoxical elevation in certain inflammatory diseases. This biological marker, which is easy to obtain, could therefore become part of standardized geriatric assessment, particularly in oncogeriatrics, in order to guide diagnostic and prognostic strategy. The systematic inclusion of vitamin B12 assays in the general assessment of elderly patients, particularly in oncology settings, deserves to be reassessed.